Using a novel NQO1 bioactivatable drug, beta‐lapachone (ARQ761), to enhance chemotherapeutic effects by metabolic modulation in pancreatic cancer. Issue 1 (27th March 2017) - Beg, Muhammad Shaalan; Huang, Xiumei; Silvers, Molly A.; Gerber, David E.; Bolluyt, Joyce; Sarode, Venetia; Fattah, Farjana; Deberardinis, Ralph J.; Merritt, Matthew E.; Xie, Xian‐Jin; Leff, Richard; Laheru, Daniel; et al.
Abstract : Novel, tumor‐selective therapies are needed to increase the survival rate of pancreatic cancer patients. K‐Ras‐mutant‐driven NAD(P)H:quinone oxidoreductase 1 (NQO1) is over‐expressed in pancreatic tumor versus associated normal tissue, while catalase expression is lowered compared to levels in associated normal pancreas tissue. ARQ761 undergoes a robust, futile redox cycle in NQO1+ cancer cells, producing massive hydrogen peroxide (H2 O2 ) levels; normal tissues are spared by low NQO1 and high catalase expression. DNA damage created by ARQ761 in pancreatic cancer cells "hyperactivates" PARP1, causing metabolic catastrophe and NAD ± keresis cell death. NQO1: catalase levels (high in tumor, low in normal tissue) are an attractive therapeutic window to treat pancreatic cancer. Based on a growing body of literature, we are leading a clinical trial to evaluate the combination of ARQ761 and chemotherapy in patients with pancreatic cancer.